2023
DOI: 10.1108/bpmj-08-2022-0409
|View full text |Cite
|
Sign up to set email alerts
|

Robotic process automation and artificial intelligence capabilities driving digital strategy: a resource-based view

Osvaldo Braz dos Santos Moderno,
Antonio Carlos Braz,
Paulo Tromboni de Souza Nascimento

Abstract: PurposeResearch of currently limited literature sees Robotic Process Automation (RPA) as an important tool at the tactical level. However, the literature has not considered its potential contribution to creating competitive advantages. This paper aims to link RPA and Resource-based view (RBV) literature, proposing a conceptual framework boosting RPA research as part of an organizational AI strategy.Design/methodology/approach This study applied a Systematic Literature Review (SRL), combining bibliometrics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…By examining existing processes and optimizing redundancies, a firm can garner a competitive edge and create a business adaptable to future radical technologies. In the work by Moderno et al (2023) the authors find that beginning with this technology and combining it with existing resources will optimize firms, as well as create a path to a technical competitive edge in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By examining existing processes and optimizing redundancies, a firm can garner a competitive edge and create a business adaptable to future radical technologies. In the work by Moderno et al (2023) the authors find that beginning with this technology and combining it with existing resources will optimize firms, as well as create a path to a technical competitive edge in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In their empirical work, Moderno et al (2023) found that combining robotic process automation with existing business infrastructure improves not only efficiency and productivity, but also the IT system itself. By adding this resource, firms will begin a continuous process of developing further resources and knowledge to incorporate more advanced technologies at a more rapid rate in a cumulative process.…”
Section: Robotic Process Automation and Ai: A Resource-based Viewmentioning
confidence: 99%
See 2 more Smart Citations